Rhetorical Styles of the Theoretical Framework in Thesis Reports of English Language Education Students: Problems and Suggested Actions - Purnawan, Ari; Margana, Margana; Putro, Nur Hidayanto Pancoro Setyo; Rasman, Rasman; Fitrianingsih, Ihtiara (JOLLT Journal of Languages and Language Teaching, 2024)
This paper began with concerns about the lacks of sharp rhetorical styles in writing, the methods of citing references, and the formulations of theories and arguments within the conceptual framework in thesis reports written by students of the English Language Education Department. The study was carried out to explain the rhetorical styles of students’ theoretical framework in their thesis report, to reveal weaknesses or the lack of strong arguments in conveying ideas in a straightforward and structured manner, and to suggest actions to prevent the problem form reoccurring in the future. The data were collected from the final project manuscripts written by students of the English Education Study Program, totaling 110 works. The analysis followed the stages of data collection, data display, data reduction and drawing conclusions. The general results of the research showed that the students did not include too many elements of critical thinking in their thesis literature review. In general, they used attribution quite excessively (78%), followed by elements of establishing links between sources (15%), and comparing their own findings or interpretations with other sources 4%. Meanwhile, the elements of application, evaluation, and statement of use had the smallest portion, each 1%. Problems found in the sample were listed based on the comparison between the data and the standard commonly used to regulate the procedure of writing a scientific paper. Recommendations were then formulated which can be used as guidelines for final project writers or any other parties related to writing scientific papers in general; they are training students of the importance of using all rhetorical styles in their citation when preparing a strong conceptual framework.